Determinação de elementos traços em carbeto de boro de alta pureza por SS-GFAAS e comparação estatística com resultados de diferentes procedimentos de decomposição - Müller, Edson Irineu (2008)
In this work a procedure is proposed for determination of Al, Cr, Cu, Mg, Mn and Ni in boron carbide samples by solid sampling graphite furnace atomic absorption spectrometry (SS-GFAAS). The samples, ESK and PL360, were digested using different decomposition procedures: wet decomposition using medium and high pressure system and alkaline fusion. The complete samples decomposition was only verified in the alkaline fusion, however high blank values for some analytes were obtained. The solutions obtained from the decomposition in high pressure system using HNO3 were analyzed and no significant difference was observed in relation to the values obtained by alkaline coalition. For SS-GFAAS, the pyrolysis and atomization curves and atomization for the boron carbide samples and reference solution were obtained. As difference was not observed in the thermal behavior of the analytes in solution and in the solid samples, the analytic curves were built with reference solutions. Besides, Zeeman's corrector was used with variable magnetic field for the construction of analytic curves with larger range concentration, making possible the analysis of samples with different concentrations. The sample homogeneity was verified by the calculation of the homogeneity constant. The results obtained by SS-GFAAS were compared (variance analysis, ANOVA) with the results obtained by wet decomposition (medium and high pressure) and alkaline fusion. Relative standard deviations smaller than 23% and detection limits between 10 to 1000 ng g-1 were obtained by SS-GFAAS. Except for Cu in the PL360 sample, for the other analytes homogeneity constant smaller than 10 were obtained, evidencing a good homogeneity. There was not significant difference (95% confidence level) for the results obtained for Al, Cu, Cr, Mg, Mn and Ni when compared the with the procedures using wet decomposition in high pressure system, alkaline fusion and SS-GFAAS.